Analisis Kelayakan Usaha Produksi Kerupuk Tempe Di Kecamatan Langsa Barat Kota Langsa - Desy Pratiwi; Hanisah; Gustiana, Cut (Jurnal Penelitian Agrisamudra, 2023)
This study aims to analyze the profitability and feasibility of tempe production in Paya Bujok Beuramo Village, West Langsa District, Langsa City. This research was conducted using a survey method. This research was conducted in Paya Bujok Beuramo Village, West Langsa District, Langsa City. The scope of this research is to analyze the feasibility of Tempe Cracker Production Business in West Langsa District, Langsa City. The time of the study was carried out from September to October 2021. The results of the financial feasibility analysis using 2 (two) assessment criteria for the tempe cracker production business in West Langsa District, Langsa City were feasible. Financial feasibility in this study is R/C, which is the ratio of total revenue to total production costs that is greater than one, which has a ratio of 1.40, or 1.40 > 1, so it can be concluded that this tempe cracker business can be said to be profitable. and worth running. Likewise the calculation of BEP, the total value of revenue is Rp. 44,064,000.00 > BEP Revenue Rp. 4,216,490.72, Production value is 2,592 Kg > Production BEP 248.03 Kg and Price value is Rp. 17,000 > BEP Price Rp. 12126.77. Thus, it can be concluded that the tempe cracker business is profitable and feasible.